Effects of a 90-min educational intervention for patients with insect venom allergy: a prospective controlled pilot study - Schoeben, Lisa-Sophie; Mohr, Nicole; Bubak, Corinna; Schmieder, Astrid; Schaarschmidt, Marthe-Lisa (Allergy, asthma and clinical immunology, 2021)
Anaphylactic sting reactions need a prompt management. A structured educational intervention for patients with insect sting allergy has not been implemented so far. The purpose of this study was to analyze the effects of a structured 90-min educational intervention for patients with insect sting allergy.